Niche differentiation of ammonia oxidizers and nitrite oxidizers in rice paddy soil. (25th February 2013) - Ke, Xiubin; Angel, Roey; Lu, Yahai; Conrad, Ralf
Summary The dynamics of populations and activities of ammonia‐oxidizing and nitrite‐oxidizing microorganisms were investigated in rice microcosms treated with two levels of nitrogen. Different soil compartments (surface, bulk, rhizospheric soil) and roots (young and old roots) were collected at three time points (the panicle initiation, heading and maturity periods) of the season. The population dynamics of bacterial (AOB) and archaeal (AOA) ammonia oxidizers was assayed by determining the abundance (using qPCR) and composition (using T‐RFLP and cloning/sequencing) of their amoA genes (coding for a subunit of ammonia monooxygenase), that of nitrite oxidizers (NOB) by quantifying the nxrA gene (coding for a subunit of nitrite oxidase of Nitrobacter spp.) and the 16S rRNA gene of Nitrospira spp. The activity of the nitrifiers was determined by measuring the rates of potential ammonia oxidation and nitrite oxidation and by quantifying the copy numbers of amoA and nxrA transcripts. Potential nitrite oxidation activity was much higher than potential ammonia oxidation activity and was not directly affected by nitrogen amendment demonstrating the importance of ammonia oxidizers as pace makers for nitrite oxidizer populations. Marked differences in the distribution of bacterial and archaeal ammonia oxidizers, and of Nitrobacter‐like and Nitrospira‐like nitrite oxidizers were found in the different compartments of planted paddy soil indicating niche differentiation. In bulk soil, ammonia‐oxidizing bacteria (Nitrosospira and Nitrosomonas) were at low abundance and displayed no activity, but in surface soil their activity and abundance was high. Nitrite oxidation in surface soil was dominated by Nitrospira spp. By contrast, ammonia‐oxidizing Thaumarchaeota and Nitrobacter spp. seemed to dominate nitrification in rhizospheric soil and on rice roots. In contrast to soil compartment, the level of N fertilization and the time point of sampling had only little effect on the abundance, composition and activity of the nitrifying communities. The results of our study show that in rice fields population dynamics and activity of nitrifiers is mainly differentiated by the soil compartments rather than by nitrogen amendment or season.